Elevated neutrophil elastase and myeloperoxidase mRNA expressions in patients with metabolic syndrome: a cross-sectional study - Zaman, Mohammad Shiblee; Naher, Sabikun; Anwar, Taznuva; Sejooti, Shabnam S.; Ahmed, Rumana; Ali, Mohammad; Muna, Farzana Z.; Yadav, Rakhee; Ranjan, Piyush; Mir, Riyaz A. (International Journal of Research in Medical Sciences, 2025)
Background: Neutrophil-derived enzymes such as neutrophil elastase (NE) and myeloperoxidase (MPO) contribute to inflammation and vascular dysfunction. However, their expression in relation to metabolic syndrome (MetS) remains underexplored. Methods: In this cross-sectional study, NE and MPO mRNA expression were evaluated in peripheral blood leukocytes of 44 adults. Among them 19 had MetS and 25 served as controls. Baseline metabolic parameters were compared between groups, and expression levels were analyzed using RT-qPCR. Results: Individuals with MetS had significantly higher systolic blood pressure, waist circumference, triglycerides, and lipid ratios (TC: HDL-C, LDL-C: HDL-C), and lower HDL-C compared to controls. NE and MPO mRNA expression were significantly elevated in MetS (p=0.015 and p=0.029, respectively). Furthermore, both NE and MPO expression showed significant moderate positive correlations with MetS status. Conclusion: Elevated NE and MPO gene expressions in peripheral blood leukocytes are associated with MetS, supporting their potential role as biomarkers of obesity-related dyslipidemia and inflammation. These findings highlight neutrophil activation as a possible molecular contributor to the pathogenesis of MetS.